Financial and non-financial disclosures on sustainable development: The mediating role of environmental accounting disclosure practices - Md. Saheb Ali Mondal; Nazma Akter; Sadia Jahan Moni; Mohammad Rashed Hasan Polas (International Journal of Financial, Accounting, and Management, 2023)
Purpose: Environmental accounting is a complementary and contributory component of corporate governance that can achieve sustainable growth and development. This study investigates the financial and non-financial disclosures that influence sustainable development through the mediating effect of environmental accounting disclosure practices. Research methodology: Self-administered questions in a closed-ended questionnaire were used, employing a five-point Likert scale to quantify opinions. Data were collected purposively and physically by the researchers from 338 respondents using a pretesting modified process, a pilot survey, a final survey, and finally analyzed using the PLS-SEM. Results: Our study reveals that non-financial disclosure has both direct and indirect effects on sustainable development through environmental accounting disclosure practices, while financial disclosure only has indirect effects. Environmental accounting disclosure practices exert a statistically significant influence and predictive power on sustainable development. Conclusion: Environmental accounting mediates the effect of corporate disclosures on sustainable development. Non-financial disclosures have stronger impacts, while financial disclosures influence sustainability indirectly. Strengthening environmental accounting supports long-term sustainability. Limitations: Our study is limited to listed textile companies, without considering non-listed textiles, ready-made garments (RMG), and other listed manufacturing companies in Bangladesh. Contributions: The study findings convey  a meaningful message to listed textile companies, their managers, researchers, regulators, and practitioners, urging them to integrate and enhance environmental practices for sustainability. These findings contribute significantly to the literature and may influence multinational buying companies.